Gene order evolution and genomic analyses of the model eukaryote, Saccharomyces cerevisiae, and other yeast species - Seoighe, Cathal (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2000)
The complete genome sequence of the yeast Saccharomyces cerevisiae can be used to form a clearer picture of the evolution of the diverse species of yeast and to construct a model of eukaryote genome evolution. In this study changes in the order of genes on yeast chromosomes were assessed and quantified by comparison with available sequence data from other yeast species and by the adaptation of comparative gene order techniques to the case of intraspecific comparative mapping within the S. cerevisiae genome. This is suggested by the hypothesis of genome duplication in the lineage leading to S. cerevisiae. Methods were developed to optimise the detection and display of cluster homology regions in an ancient tetraploid. A fresh look was taken at outstanding questions of genome organisation that have remained unresolved since the beginning of the yeast sequencing project. Compositional variation in yeast was shown to be explainable by short range correlation in base com position and no evidence was found for periodic variation in base composition over long distances. The available contiguous sequences from the pathogenic yeast Canciicia albicans, spanning most of the genome, were compared to S. cerevisiae and a large number of small inversions of gene order were found. The excess of small rearrangements of gene order has implications for comparative mapping and for the quantitative methods that have been applied to gene order comparison.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin